ROS Architecture for Nonlinear Control in Singularly Perturbed Wheeled Mobile Robots: Dynamic Confined Space-Based Approach - Fernández, César; Cunha, Amanda (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The research reported here presents the development of an open architecture that enables the integration of actuators level controllers (e.g., Arduino-based platforms) with the ROS framework, which can be used as a starting point and easily generalized for a wide variety of robots. To this end, the architecture is based on three layers, the actuators level controllers, the high-level nonlinear controllers and the middle layer. This last one also assumed as being an interface, which is used to communicate actuators level controllers with high-level controllers aiming small delays in the communication. To validate such approach, it will be considered the classical control by using static state-feedback linearization whose robustness with respect to the deformability of the wheel will be based on singular perturbations methods (specifically the flexibility, which is represented by ε) and corrective control actions based on the approach in [22]. The results show that the performance of the controller is increased when the degree of the corrective control is also increased as well as the suitable distribution of the architecture into the nodes of the ROS approach.